2012
DOI: 10.1016/j.otsr.2012.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Anterolateral kyphoplasty in the management of cervical spinal metastasis

Abstract: Management of spinal metastasis is still controversial and must take into account various parameters. The aim of this study is to report the technical feasibility of a less invasive anterior cervical balloon kyphoplasty for vertebral body reinforcement. Six consecutive patients with an osteolytic cervical metastasis, without neurologic compromise, and for whom a curative treatment was not indicated, were retrospectively reviewed. All patients underwent balloon kyphoplasty through a small anterolateral cervicot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 18 publications
0
20
0
Order By: Relevance
“…The preoperative pain value of 6.0/10 on the VAS was comparable to scores in other published studies, as were the postoperative values (2.9/10) at Day 2 after surgery and at the follow-up (0.5/10). 5,18,32,37,45 We showed that this significant reduction in neck pain occurred despite having performed in the cervical spine additional dorsal procedures in 2 cases and additional ventral procedures in 5 cases.…”
Section: Discussionmentioning
confidence: 85%
“…The preoperative pain value of 6.0/10 on the VAS was comparable to scores in other published studies, as were the postoperative values (2.9/10) at Day 2 after surgery and at the follow-up (0.5/10). 5,18,32,37,45 We showed that this significant reduction in neck pain occurred despite having performed in the cervical spine additional dorsal procedures in 2 cases and additional ventral procedures in 5 cases.…”
Section: Discussionmentioning
confidence: 85%
“…In the upper cervical spine, this procedure is challenging for the surgeon to control using the anterolateral, posterolateral, translateral, and direct transoral approaches. 43 48 Indications for kyphoplasty include painful vertebral metastases without spinal instability, and spinal cord and spinal nerve root compression. Therefore, the purpose of the operation is to stabilize the cervical spine and relieve intractable pain.…”
Section: Discussionmentioning
confidence: 99%
“…Case series and reports suggest that vertebroplasty and kyphoplasty in the cervical spine can be used to treat painful metastatic deposits. 3 7 This is usually advocated through a minimal anterior approach to minimize the risks of percutaneous trocar insertion.…”
Section: Discussionmentioning
confidence: 99%
“…Although cement leak is a reported complication of this technique, it is most often not clinically significant. 3 …”
Section: Introductionmentioning
confidence: 99%